Pleomorphic Adenoma of the Soft Palate: Case Report - Yuliya Menchisheva; Saule Mussabekova; Dana Menzhanova; Shynggys Duisenbay; Magomed Khairoyev; Kamil Zubanov (Case Reports in Medicine)
Conclusion: Pleomorphic adenoma of the palate is an important entity to consider in the differential diagnosis of salivary gland neoplasms. Early recognition and complete surgical removal are key to preventing recurrence and malignant transformation.